Development of the AGIL Model for Elderly Survival at the Association of the Elderly at GPIB Tamansari, GKJ 55, and GPDI Siloam in the city of Salatiga - Suwartiningsih, Sri; Sampoerno; Desi; Sugiarto, Marchus; Gaol, Friska Haliani L. (International Journal of Science and Society, 2025)
Some churches in Salatiga have fellowships for the elderly. These fellowships are named differently: in the Protestant Church in Western Indonesia (GPIB) Tamansari Salatiga, it is called PKLU (Fellowship of the Elderly); in GKJ 55, it is named Persekutuan Adiyuswo; and in the Pentecostal Church in Indonesia (GPDI) Siloam, it is referred to as Kaum Usia Lanjut. Old age is a period when individuals reach maturity in the life process. During this stage, individuals experience various changes and challenges, including adapting to old age, achieving life goals, integrating into their surroundings, and maintaining patterns in their personal and communal lives. Some elderly fellowships make individuals feel uncomfortable and withdraw from activities, while others motivate them to continue participating. This study aims to develop the AGIL concept, which includes adaptation, goal attainment, integration, and latent pattern maintenance, to support the sustainability of the elderly fellowship at GKJ 55, GPIB Tamansari, and GPDI Siloam in Salatiga. The research employs a qualitative-constructive method. The results show that the elderly adapt both as leaders and members of the fellowship. The purpose of participating in these fellowships is to socialize with fellow seniors, communicate, feel happy, and enjoy themselves. Integration among elderly members and leaders is evident in every fellowship activity. Pattern maintenance is achieved through the continuity of monthly fellowship and worship services, ensuring the sustainability of the elderly fellowship at GKJ 55, GPIB Tamansari, and GPDI Siloam in Salatiga.